Behavioral and biochemical consequences after chronic exposition to the herbicide atrazine in tadpoles - Ikari, Fernanda Lie; Viriato, Cristina [UNESP]; França, Fernanda Menezes; Marcantonio, Adriana Sacioto; Bach, Erna Elizabeth; Badaró-Pedroso, Cintia; Ferreira, Cláudia Maris (Taylor & Francis, 2024)
Atrazine (ATZ) is the third most sold herbicide in Brazil, occupying the seventh position between most widely used pesticides. Due to its easy outflow, low reactivity and solubility, moderate adsorption to organic matter and clay, and long soil persistence, residual herbicide can be identified after long periods following application, and its usage has been prohibited in diverse countries. Amphibians are important bioindicators to assess impact of pesticide like atrazine, due to having a partial aquatic life cycle. This study had as objective to assess the response of bullfrog (Lithobates catesbeianus) tadpoles when exposed to this herbicide. Animals were exposed for a total of 168h to following concentrations: negative control, 40 μg/L, 200 μg/L, 2000 μg/L, 20000 μg/L of ATZ. Analysis of swimming activity was performed, and biochemical profile was assessed by analysis of blood and plasma glucose levels, urea, creatinine, cholesterol, HDL, triglycerides, glutamic pyruvic transaminase (GPT), alkaline phosphatase (AP), calcium, total proteins, phenol, peroxidase and polyphenol oxidase activity. Results exhibited malnutrition, anemia, likely muscle mass loss, and hepatic damage, indicating that ATZ can lead to an increase in energy to maintain homeostasis for animal survival.
Keywords: biomarkers; blood plasma; ecotoxicology; Pesticides